2010
DOI: 10.2478/abm-2010-0119
|View full text |Cite
|
Sign up to set email alerts
|

Osteoinductive potential of small intestinal submucosa/ demineralized bone matrix as composite scaffolds for bone tissue engineering

Abstract: Background: Demineralized bone matrix (DBM) is extensively used in orthopedic, periodontal, and maxillofacial application and investigated as a material to induce new bone formation. Small intestinal submucosa (SIS) derived from the submucosa layer of porcine intestine has widely utilized as biomaterial with minimum immune response. Objectives: Determine the osteoinductive potential of SIS, DBM, SIS/DBM composites in the in vitro cell culture and in vivo animal bioassays for bone tissue engineering. Materials … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2012
2012
2021
2021

Publication Types

Select...
3

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(5 citation statements)
references
References 27 publications
0
5
0
Order By: Relevance
“…Moreover, collagen scaffolds with incorporated DBM could enhance cell attachment, stimulate cell proliferation, and promote osteogenic differentiation [ 12 ]. Additionally, DBM combined with small intestinal submucosa composite exhibited superior osteoinductivity, provided a suitable environment for osteoblast differentiation, and ultimately enhanced new bone formation [ 25 ]. Our findings from this study are in accordance with reports from recent studies, although different scaffolds were used.…”
Section: Discussionmentioning
confidence: 99%
“…Moreover, collagen scaffolds with incorporated DBM could enhance cell attachment, stimulate cell proliferation, and promote osteogenic differentiation [ 12 ]. Additionally, DBM combined with small intestinal submucosa composite exhibited superior osteoinductivity, provided a suitable environment for osteoblast differentiation, and ultimately enhanced new bone formation [ 25 ]. Our findings from this study are in accordance with reports from recent studies, although different scaffolds were used.…”
Section: Discussionmentioning
confidence: 99%
“…In one study, although SIS without cell seeding resulted in no new bone formation in vivo , whereas DBM alone demonstrated new bone formation along the edge of old DBM particles, an SIS/DBM composite exhibited higher osteoinductivity. Moreover, the residual SIS/DBM was surrounded by an osteoid-like matrix and newly formed bone [527]. The capacity for localized collagen formation and osteocalcin deposition by SIS-ECM was demonstrated in a full-thickness bilateral bone-defect model in rat crania; the defects were managed with SIS sponges, and the presence of bone marrow-derived stem cells (BMSCs) resulted in significantly greater bone formation [528].…”
Section: Human Tissue Ecm-based Biomaterialsmentioning
confidence: 99%
“…132,135 In addition to these native ECM molecules, the collagen fiber orientation that is maintained after the decell process has also attracted attention. 132 Both of these inherent properties have sparked strategies employing SIS as scaffolds in the fields of cardiovascular, [137][138][139][140] bone, [141][142][143] nerve, 144 soft tissue, 86,87,145 and urogenital [146][147][148][149] tissue engineering (Table 6). Currently, SIS is Food and Drug Administration (FDA) approved for several urogenital applications, including hernia repair.…”
Section: Small Intestinal Submucosamentioning
confidence: 99%
“…132 The presence of aligned collagen fibers and endogenous growth factors remaining in the acellular SIS matrix has sparked interest within the bone tissue engineering community as well. Kim et al 142 and Honsawek et al 141 showed that SIS scaffolds promoted new bone formation in a rat model. Zhao et al 143 found similar results in a rabbit model when SIS was seeded with MSCs.…”
Section: Small Intestinal Submucosamentioning
confidence: 99%
See 1 more Smart Citation